2020
DOI: 10.1107/s2053273320009584
|View full text |Cite
|
Sign up to set email alerts
|

Fast analytical evaluation of intermolecular electrostatic interaction energies using the pseudoatom representation of the electron density. III. Application to crystal structures via the Ewald and direct summation methods

Abstract: The previously reported exact potential and multipole moment (EP/MM) method for fast and accurate evaluation of the intermolecular electrostatic interaction energies using the pseudoatom representation of the electron density [Volkov, Koritsanszky & Coppens (2004). Chem. Phys. Lett. 391, 170–175; Nguyen, Kisiel & Volkov (2018). Acta Cryst. A74, 524–536; Nguyen & Volkov (2019). Acta Cryst. A75, 448–464] is extended to the calculation of electrostatic interaction energies in molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 133 publications
(198 reference statements)
1
11
0
Order By: Relevance
“…The R aMM parameter governs the distance at which the EP/ MM method switches the evaluation of the ESP, EF and EFG from the exact formulae (exact potential) to the atomic multipole moment (aMM) approximation Nguyen et al, 2018;Nguyen & Volkov, 2019). We note that a thorough numerical analysis for the choice of the R aMM parameter when calculating the intermolecular electrostatic interaction energies performed in Paper III suggested an optimal precision/performance value of 5 Å for the first-and second-row atoms.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The R aMM parameter governs the distance at which the EP/ MM method switches the evaluation of the ESP, EF and EFG from the exact formulae (exact potential) to the atomic multipole moment (aMM) approximation Nguyen et al, 2018;Nguyen & Volkov, 2019). We note that a thorough numerical analysis for the choice of the R aMM parameter when calculating the intermolecular electrostatic interaction energies performed in Paper III suggested an optimal precision/performance value of 5 Å for the first-and second-row atoms.…”
Section: Resultsmentioning
confidence: 97%
“…The boundary at which the exact and approximate values are expected to converge is defined by the userspecified parameter R aMM . For the intermolecular electrostatic interaction energies, the parameter R aMM was estimated to be 4-5 Å for the first-and second-row atoms Nguyen et al, 2018;Nguyen & Volkov, 2019;Nguyen et al, 2020), while for the ESP, EF and EFG the preliminary work suggested a value of 6 Å for organic systems . A more detailed and thorough analysis for the choice of R aMM in the ES/EP/MM calculations is presented in Section 5.1 below.…”
Section: Esp Ef and Efg From Atomic Multipole Momentsmentioning
confidence: 98%
See 3 more Smart Citations